Cross-species Analyses of Intra-species Behavioral Differences in Mammals and Fish. (1st March 2020) - Demin, Konstantin A.; Lakstygal, Anton M.; Volgin, Andrey D.; de Abreu, Murilo S.; Genario, Rafael; Alpyshov, Erik T.; Serikuly, Nazar; Wang, Dongmei; Wang, Jiantao; Yan, Dongni; Wang, Mengyao; Yang, LongEn; et al.
Highlights: Multiple species display robust individual behavioral variance. Intraspecies behavioral individuality is an important area of neuroscience research. Zebrafish are useful an aquatic model organism to study individual differences. Cross-species analyses of intraspecies variance is critical in experimental CNS models. Abstract: Multiple species display robust behavioral variance among individuals due to different genetic, genomic, epigenetic, neuroplasticity and environmental factors. Behavioral individuality has been extensively studied in various animal models, including rodents and other mammals. Fish, such as zebrafish ( Danio rerio ), have recently emerged as powerful aquatic model organisms with overt individual differences in behavioral, nociceptive and other CNS traits. Here, we evaluate individual behavioral differences in mammals and fish, emphasizing the importance of cross-species analyses of intraspecies variance in experimental models of normal and pathological CNS functions.